1969
DOI: 10.21236/ad0697649
|View full text |Cite
|
Sign up to set email alerts
|

Magnetometer Respirometer for Laboratory and Diving Studies

Abstract: To construct and test a system for the measurement of respiratory tidal volume and respiratory rate that avoids the limitations and disadvantages of the usual mouthpiece, face masks, and neck seals in a plethysmograph. FINDINGS A respirometer based on the use of two pairs of magnetic coils placed on the chest and abdomen, as described by Mead and co-workers, will reproducibly measure tidal volume as well as respiratory rate. APPLICATIONS This system, at its present stage of development, can be used in the labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1973
1973
1996
1996

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Concerning the behavior of gas bubbles generated by sparging, it was observed in the literature [5] that the frequency of these bubbles generated at a constant gas flow increases when the surfactant concentration increases (the dynamic surface tension decreases). On the other hand, it was observed that, if the surfactant concentration is maintained constant (constant dynamic surface tension), the bubble frequency increases when the gas flow is increased [6].…”
Section: O" = -~Agmentioning
confidence: 99%
“…Concerning the behavior of gas bubbles generated by sparging, it was observed in the literature [5] that the frequency of these bubbles generated at a constant gas flow increases when the surfactant concentration increases (the dynamic surface tension decreases). On the other hand, it was observed that, if the surfactant concentration is maintained constant (constant dynamic surface tension), the bubble frequency increases when the gas flow is increased [6].…”
Section: O" = -~Agmentioning
confidence: 99%
“…Concerning the behaviour of gas bubbles generated by sparging, it was observed in literature [5] that the frequency of these bubbles generated at a constant gas flow increases when the surfactant concentration increases (the dynamic surface tension decreases). On the other hand, it was observed that, if the surfactant concentration is maintained constant (constant dynamic surface tension), the bubble frequency increases when the gas flow is increased [6].…”
Section: O = --A Gmentioning
confidence: 99%